Pengaruh Ukuran Perusahaan Dan Pertumbuhan Penjualan Terhadap Financial Distress Pada Perusahaan Textile Dan Garment Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Astuti, Winda; Priyanto, Aria Aji (Manajemen & Bisnis Jurnal, 2025)
This study aims to determine the effect of company size and sales growth on financial distress in Textile and Garment companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The type of research used is quantitative with an associative approach. The population used in this study is Textile and Garment companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period with a sample of 7 companies. The sampling technique uses the purposive sampling method. The data analysis method uses descriptive analysis, model suitability testing, panel data regression analysis and hypothesis testing (Partial t test and simultaneous F test) with the help of Eviews 12. The results of this study indicate that company size has a significant effect on financial distress with the results of the t test obtained t count 2.516938> 2.03452 t table and Prob. significance of 0.0170 <0.05. Sales growth does not have a significant effect on financial distress with the results of the t-test obtained t count 1.147534 < 2.03452 t table and Prob. significance of 0.2597 > 0.05. Company size and sales growth have a significant effect together on financial distress, with the results of the F test obtained F count 3.538817 > 3.28 F table and Prob. significance of 0.040883 < 0.05